Phase behavior of nematic-nanoparticle mixtures - Hölbl, Arbresha; Ranjkesh, Amid; Abina, Andreja; Kralj, Samo; Zidanšek, Aleksander (Frontiers in Soft Matter, 2023)
We study the effects of nanoparticles (NPs) on thermotropic nematic liquid crystals (LCs) in relatively dilute NP–LC mixtures. We are interested in the fundamental generic mechanisms that quantitatively and qualitatively affect the phase behavior of LCs. A simple molecular field analysis shows that a phase transition will likely occur upon entry into the ordered phase. Moreover, the interaction between nematogenic NPs and LCs could force a sergeant–soldier-like behavior, in which only the phase behavior of one component is affected despite the symmetric appearance of the coupling term. When NPs are anisotropic, their influence on LC phase behavior can be qualitatively different depending on the anchoring, even in the absence of the disorder. We illustrate numerically that a random-field-type disorder might impose either short-range, quasi-long-range, or even long-range order, which might survive.